The Efficiency of Indigofera Leaves Meal Hydrolysate Utilization on Growth Performance of Leptobarbus hoevenii - Rakhmawati, Rakhmawati; Indariyanti, Nur; Sofiana, Anjar; Kurniawan, Agung (Journal Omni-Akuatika, 2023)
This study was conducted to evaluate the efficacy of indigofera leaves meal hydrolysate (ILMH) on growth Leptobarbus hoevenii growth. This study employed five dietary treatments with varying levels of ILMH. Cellulase enzymes were used to hydrolyze Indigofera leaf meal, which was then combined with other feed ingredients. Three replicates of feed without ILMH, 10% ILMH, 20% ILMH, 30% ILMH, and 35% ILMH were included in the treatment-examination feed. Average initial fish weight was 1.27±0.01 g, and initial length was 4.28±0.07 cm. Weight observation was also conducted every two weeks. After six weeks of rearing, survival, final biomass, specific growth rate, and feed efficiency  were observed. At the beginning and the end of maintenance, temperature, pH, and dissolved oxygen measurements were taken to determine the water's quality. Results that that the utilization of ILMH in L. hoevenii feed could substitute the use of soybean meal for 10-35% of the feed. Among all treatments, 10% ILMH-containing feed resulted in the highest growth and feed efficiency. This treatment had a 100% survival rate, a 1.78±0.05% specific growth rate, and a 53.28 ± 1.59% feed efficiency. According to the findings of this study, the utilization of 10% hydrolysate of indigofera leaf meal in feed was effective in enhancing L. hoevenii’s growth performance.  Keywords: Efficiency, indigofera leaves, Leptobarbus hoevenii, hydrolysate, growth